2011
DOI: 10.1007/s12149-011-0558-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycosylation on biodistribution of radiolabeled glucagon-like peptide 1

Abstract: Objective Glycosylation is generally applicable as a strategy for increasing the activity of bioactive proteins. In this study, we examined the effect of glycosylation on biodistribution of radiolabeled glucagon-like peptide 1 (GLP-1) as a bioactive peptide for type 2 diabetes.Methods Noninvasive imaging studies were performed using a gamma camera after the Conclusions This study demonstrated that glycosylation significantly decreased the distribution of radiolabeled GLP-1 into the liver and increased the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Glycosylation is a promising strategy for improving the biodistribution and poor pharmacokinetic profile of radiolabeled peptides for diagnostic and therapeutic purposes 82. The radiolabeled derivatives of the bombesin peptide have potential applications in cancer cell imaging and peptide receptor radiotherapy.…”
Section: Development Of Therapeutic Peptides Using Glycosylation Stramentioning
confidence: 99%
“…Glycosylation is a promising strategy for improving the biodistribution and poor pharmacokinetic profile of radiolabeled peptides for diagnostic and therapeutic purposes 82. The radiolabeled derivatives of the bombesin peptide have potential applications in cancer cell imaging and peptide receptor radiotherapy.…”
Section: Development Of Therapeutic Peptides Using Glycosylation Stramentioning
confidence: 99%
“…For example, studies showed that the additional sugar moieties boost the analgesic activity (Masand et al, 2006;Polt et al, 1994), an antinociceptive effect similar to morphine (Bilsky et al, 2000), both in maximal analgesic level and the analgesia duration (Egleton et al, 2001). On another aspect, radiolabeled glycopeptides affect the biodistribution in the application to cancer cell imaging (Schweinsberg et al, 2008;Watanabe et al, 2012), including less liver and renal accumulation and improvement in tumor uptake, leading to a minimum effective dosage and an increased tumor-to-background ratio in imaging (Haubner et al, 2001;Schottelius, Wester, Reubi, Senekowitsch-Schmidtke, & Schwaiger, 2002). Besides functioning as potential therapeutic drugs, O-glycosylated peptide toxins, Vespulakinins, isolated from yellowjacket venom sacs were the first reported vasoactive glycopeptides and naturally occurring glycosylated derivatives of bradykinin, with an identical C-terminus sequence (Yoshida, Geller, & Pisano, 1976).…”
Section: Introductionmentioning
confidence: 99%